UPAYA MENGURANGI OVERCROWDED LEMBAGA PEMASYARAKATAN PADA MASA PANDEMI COVID-19 DAN OPTIMALISASI PEMBINAAN DI MASA MENDATANG - Terry Ichwal Nurrohman; Padmono Wibowo (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Overcrowded occurs due to an increase in the number of prisoners who are more than the capacity of the available prisons. Overcrowded increases the risk of Covid-19 transmission in prisons. In order to minimize the spread of Covid-19 , the government issued a policy of assimilation and social integration towards the release of prisoners and children. This study discusses problems related to overcrowded in correctional institutions and their relation to the policy of releasing prisoners in order to accelerate social reintegration, and proposes ideas related to efforts to reduce overcrowded.in the future. This research uses normative ( doctrinal ) research . The results showed that there is a need for policies that accelerate the reintegration process of prisoners. The correctional guidance system must also focus more on the recognition and protection of human rights of the prisoners themselves. The good time allowance model is recommended for maximum development of prisoners. The model emphasizes reducing the length of stay in the correctional facility on condition that they do good deeds or work and have a strong commitment to be better. This can encourage programs to accelerate social reintegration and accustom inmates to not repeating past bad deeds..